Chemical synthesis of left arm of Chlamydomonas reinhardtii mitochondrial genome and in vivo functional analysis - Wang, Quan; Luo, Haolin; Zhuang, Jieyi; Li, Xinyi; Huang, Danqiong; Hu, Zhangli; Zhang, Guiying (Frontiers in Microbiology, 2022)
Chlamydomonas reinhardtii is a photosynthetic eukaryote showing great industrial potential. The synthesis and in vivo function of the artificial C. reinhardtii genome not only promotes the development of synthetic biology technology but also supports industries that utilize this algae. Mitochondrial genome (MtG) is the smallest and simplest genome of C. reinhardtii that suits synthetic exploration. In this article, we designed and assembled a synthetic mitochondria left arm (syn-LA) genome sharing >92% similarity to the original mitochondria genome (OMtG) left arm, transferred it into the respiratory defect strain cc-2654, screened syn-LA containing transformants from recovered dark-growth defects using PCR amplification, verified internal function of syn-LA via western blot, detected heteroplasmic ratio of syn-LA, tried promoting syn-LA into homoplasmic status with paromomycin stress, and discussed the main limitations and potential solutions for this area of research. This research supports the functionalization of a synthetic mitochondrial genome in living cells. Although further research is needed, this article nevertheless provides valuable guidance for the synthesis of eukaryotic organelle genomes and opens possible directions for future research.